2012
DOI: 10.1016/j.cellimm.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Growth, metastasis, and expression of CCL2 and CCL5 by murine mammary carcinomas are dependent upon Myd88

Abstract: Previously we reported that lipopolysaccharide (LPS) treatment of murine mammary carcinomas resulted in decreased growth of the tumors. Here we show the decreased growth following LPS treatment was mediated through effects downstream of TLR4 and Myd88. Perhaps more notably, simply reducing TLR4 or Myd88 levels was sufficient to slow tumor growth rates. Moreover, reduced levels of Myd88 correlated with a significant reduction in lung metastasis as well as decreased CCL2 and CCL5 expression. To determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
3
28
1
Order By: Relevance
“…In particular, MyD88 is required for nerve injury induced upregulation of CCL2, in DRG neurons (Fig. 6E,F), consistent with another report in which the release of CCL2 was dependent on MyD88 pathway in murine mammary carcinomas cells23. Previous studies showed that CCL2, upregulated in DRG neurons after nerve injury27, could increase Na v 1.8 activity and excitability of DRG neurons22, leading to an enhanced neuropathic pain state.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, MyD88 is required for nerve injury induced upregulation of CCL2, in DRG neurons (Fig. 6E,F), consistent with another report in which the release of CCL2 was dependent on MyD88 pathway in murine mammary carcinomas cells23. Previous studies showed that CCL2, upregulated in DRG neurons after nerve injury27, could increase Na v 1.8 activity and excitability of DRG neurons22, leading to an enhanced neuropathic pain state.…”
Section: Discussionsupporting
confidence: 90%
“…CCL2 was shown to increase Na v 1.8 activity and excitability of DRG neurons2122. Notably, CCL2 expression was found to be dependent on MyD88 in murine mammary carcinomas cells23. We postulated that primary sensory neurons recruit macrophages to DRGs through chemokine release.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, it has also been revealed that tumor protein p53 binds to CCL2, consequently significantly downregulating CCL2 promoter activity, and thus suppressing CCL2-induced subcutaneous tumor xenografts (49). CCL2 may be regulated by myeloid differentiation primary response 88 in murine mammary carcinomas and thus affect cell viability and metastasis (50). CCL2 was revealed to be involved in visfatin-mediated lung cancer NCI-H446 cells transendothelial migration and visfatin-induced CCL2 was attenuated by a specific inhibitor of PI3K/AKT signaling (51).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on tumor cell lines showed that TLR4 stimulation facilitates cell proliferation (4,5). Similarly, LPS facilitates carcinogenesis in mouse models of skin cancer (6), lung cancer (7), breast cancer (8), and colon cancer (9).…”
mentioning
confidence: 99%